1988
DOI: 10.3109/00365528809093867
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cathodic Trypsin-like Immunoreactivity, Pancreatic Lipase, and Pancreatic Isoamylase as Diagnostic Tests of Chronic Pancreatitis or Pancreatic Steatorrhea

Abstract: We compared serum concentrations of cathodic trypsin-like immunoreactivity, pancreatic lipase, and pancreatic isoamylase as diagnostic tests of chronic pancreatitis (and of pancreatic steatorrhea in the 41 patients with steatorrhea) in 105 patients (57 men, 48 women) consecutively investigated because of clinical suspicion of chronic pancreatitis. Chronic pancreatitis (36 patients), pancreatic steatorrhea (24 patients), and other diseases were diagnosed without knowledge of the serum levels of the three enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…as reported by other authors [5,6,14], The limited clinical utility of serum pancreatic enzyme determinations in the diagnosis of CP is further extended in our study by the application of ratios of different enzymes. Few studies have reported a comparison among the values of different serum pan creatic enzymes in the diagnosis of CP [1,8,14], and an analysis of the ratios of these enzymes has never been pre sented. The application of ratios between enzymes does not significantly improve the accuracy of individual se rum enzymes in detecting CP.…”
Section: Discussionsupporting
confidence: 52%
“…as reported by other authors [5,6,14], The limited clinical utility of serum pancreatic enzyme determinations in the diagnosis of CP is further extended in our study by the application of ratios of different enzymes. Few studies have reported a comparison among the values of different serum pan creatic enzymes in the diagnosis of CP [1,8,14], and an analysis of the ratios of these enzymes has never been pre sented. The application of ratios between enzymes does not significantly improve the accuracy of individual se rum enzymes in detecting CP.…”
Section: Discussionsupporting
confidence: 52%
“…Levels of IRT can be measured in blood by immunologic assays, such as RIA or ELISA. While IRT analysis is cheap, simple to perform, and risk‐free to the patients, the diagnostic value of these enzymes in a target population suspected of having chronic pancreatitis, is limited to positive test results [9]. Clinical studies on IRT have shown conflicting results.…”
Section: Discussionmentioning
confidence: 99%